Cyclic Microwave-Assisted Sol-Gel Process of BaLa2(MoO4)4:Er3+/Yb3+ Particles and their Upconversion Photoluminescence Properties - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
Er3+ doped BaLa2(MoO4)4 [BaLa2(MoO4)4:Er] and Er3+/Yb3+ co-doped BaLa2(MoO4)4 (BaLa2(MoO4)4:Er/Yb) phosphors were successfully synthesized by a cyclic microwave-assisted sol-gel process followed by heat treatment. The microstructures exhibited well-defined and homogeneous morphology with particles sizes of 2-10 μm. With excitation at 980 nm, the doped particles exhibited a strong 525 and 550 nm emission bands in the green region and a weak 655 nm emission band in the red region. Raman spectra of of the doped particles indicated the detection of additional strong peaks at higher frequencies (1000, 1040, 1092, 1138, 1175, 1238, 1362 and 1458 cm-1) and weak peaks at lower frequencies (232, 380, 568 and 660 cm-1).